Trophoblast coculture induces intercellular adhesion molecule-1 expression in uterine endometrial epithelial cells through TNF-α production: Implication of role of FSH and ICAM-1 during embryo implantation. (August 2022) - Lai, Tsung-Hsuan; Chen, Hsuan-Ting; Wu, Wen-Bin
Abstract: In humans, successful implantation requires a finely tuned synchrony between an appropriately developing embryo and the receptive endometrium, involving apposition, adhesion, and invasion. Therefore, this study was sought to establish a coculture cell model to investigate trophoblast-mediated blastocyst apposition and adhesion to endometrial epithelium events during embryo implantation. The direct contact and indirect noncontact coculture models were successfully established by using human BeWo trophoblasts and HEC-1A endometrial epithelial cells. Interestingly, a significant increase of ICAM-1 protein and mRNA expression was observed in both coculture systems when challenged with follicle-stimulating factor (FSH). In accordance with these observations, trophoblast-conditioned medium (CM) could also enhance epithelial ICAM-1 production, suggesting involvement of trophoblast-secreting factor(s) in crosstalk between two cells. Indeed, FSH stimulation enhanced TNF-α expression in the trophoblasts and epithelial ICAM-1 induction were abolished by a TNF-α blocking/neutralizing antibody (TNF-α B/N Ab). Meanwhile, the intracellular calcium, PKA/CREB, and transcription/translation signaling pathways in epithelial cells participated in the ICAM-1 induction. Finally, the trophoblast cells were more susceptible to adhesion to CM-primed epithelial cell monolayer, where the adhesion could be abolished by TNF-α B/N Ab. Therefore, we present here novel findings that coculture of trophoblast with endometrial epithelial cells in the presence of FSH leads to an increase in epithelial ICAM-1 expression and trophoblast adhesion to epithelial monolayer through stimulating trophoblast's TNF-α cytokine production. This study also addresses an important issue that a possible role of microenvironmental and exogenously-added FSH in enhancing blastocyst interaction with endometrium during embryo implantation of natural or in-vitro fertilization cycle. Graphical Abstract: ga1 Highlights: The epithelial ICAM-1 is upregulated in trophoblast-endometrial epithelial cell cocultures by FSH stimulation. The trophoblast-released TNF-α and intraepithelial calcium and PKA/CREB signaling mediate epithelial ICAM-1 induction. The novel epithelial ICAM-1 induction is functionally involved in trophoblast-endometrial epithelial cell interaction.